CARBON EMISSION ESTIMATION DUE TO LAND COVER CHANGE IN THE TROPICAL FOREST LANDSCAPE IN JAMBI PROVINCE - Melati, Dian Nuraini (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
Land use land cover change and forestry play an important role in the global environmental change. Anthropogenic activities in changing the land have caused earth surface change. This change has a role to increase the change of global greenhouse gases in the atmosphere which also causes the increase greenhouse gases emission. Land cover change and forestry are sectors which cause high carbon emission. Therefore, a study in land cover change and estimation of carbon emission becomes important. This study took place in Jambi Province where deforestation has been in a high pace. In 2009 and 2011, the dominant area is dryland agriculture mixed with bush followed by secondary forest, i.e. 25% and 18.6%, respectively (in 2009); and 37.1% and 18.9%, respectively (in 2011). For the secondary forest, the gain was caused by the conversion of dryland agriculture mixed with bush and shrub into secondary forest. The loss of secondary forest is the highest among other forest cover at around 87,765 Ha due to the conversion into bare land and dryland agriculture mixed with bush. Due to land cover change in Jambi Province, the estimation of nett emission in the period of 2009-2011 is 4.8 Mt CO2-eq/year.